Seasonal Variations of Marine Environment and Primary Production in the Taiwan Strait - Tseng, Hsiao-Chun; You, Wan-Lynn; Huang, Wei; Chung, Chih-Ching; Tsai, An-Yi; Chen, Tzong-Yueh; Lan, Kuo-Wei; Gong, Gwo-Ching (Frontiers in Marine Science, 2020)
The first data set of seasonal marine environment and euphotic zone integrated primary production (IP) variations in the Taiwan Strait was reported. The measured annual IP was 123±86 gC m-2 y-1 (338±235 mgC m-2 d-1), and its seasonal variations can be described with a left-skewed normal distribution curve. The average seasonal IP values from the highest to the lowest were summer (664±270 mgC m-2 d-1), autumn (350±118 mgC m-2 d-1), spring (202±110 mgC m-2 d-1) and winter (137±68 mgC m-2 d-1). The lowest IP was during the nutrient-rich winter because it had a short insolation duration, low incident photosynthetic active radiation (PAR) and low light transmission (shallow euphotic zone depth) due to strong vertical mixing. In contrast to the winter, the highest IP was during the nutrient-depleted summer, which had a long insolation duration, high incident PAR and high light transmission (deeper euphotic zone depth). In addition, the heterotrophic nutrients from upwelling in the south might also support the highest IP in summer. As three primary water masses exist in the Taiwan Strait and three of them have different characteristics, different mixing ratios of water masses may cause different chemical and hydrographic conditions, which leads to different levels of Chl a concentrations and primary production. It is worth to mention that offshore wind farm (OWF) construction in the Changyun Rise (CYR) of the Taiwan Strait is on-going. As primary production is the foundation for a marine ecosystem and supports the food web and fish stock, the results of this research can not only be used as the baseline for evaluating the OWF impact on the marine ecosystem but also be used for assessing their influence on fishery resources.